An Analysis of Masked Bobwhite Collection Locales and Habitat Characteristics - David E. Brown; Kevin B. Clark; Randall D. Babb; Grant Harris (National Quail Symposium Proceedings, 2017)
We evaluated the collecting locales of 251 masked bobwhite (Colinus virginianus ridgwayi) specimens in museum collections. Eighteen were from 4 sites in Arizona—all collected by Herbert Brown. The vast majority (93%) of specimens were from the Mexican State of Sonora. We visited and photographed each of the Arizona collection locations and most of the sites in Sonora. Collector descriptions indicate the bird’s principal habitat affiliations were with tall grass-weed (1⁄4 forb) pastures, savannas, and farm fields. All historic localities visited were either in grass-forb habitats along drainages or in present or former savannas adjacent to woody cover and/or agricultural fields between 240 and 1,060 m elevation. These sites were remarkably similar to other bobwhite habitats in subtropic-tropic South Texas and Oaxaca, Mexico. Masked bobwhite habitat was a diverse tropic-subtropic grassland within or adjacent to dense woody cover (thornscrub) and/or farmland. These habitats experienced alterations and loss of the tall grass-weed component due to livestock husbandry. Some former habitat sites appear to have recovered, however, and restoration of the subspecies might be possible if suitable stock exists. Unfortunately, this bird may now be functionally extinct.
Keywords: Arizona; Buenos Aires National Wildlife Refuge; Colinus virginianus ridgwayi; domestic quail; endangered species; grass; grassland; masked bobwhite; museum collections; savanna; Sonora